Análise do gerenciamento dos residuos sólidos em Panambi - RS: 1955 a 2012 - Hempe, Cléa (2013)
The general objective of this research consisted in conducting a historical and geographical review on the solid waste management from 1955 to 2012. The study was conducted using the qualitative research, where it was possible to reflect, analyze and position on the actions of the public officials. Over the city public administrations from 1955 to 2012, there were seven administrators whereas three of them managed only one term, two managed for two terms and two managed for three terms. Panambi city had three places where they held the solid waste disposal. From the theoretical framework and search through the field research it was possible to carry out the analysis where we realized that each administrator had their own concept of solid waste management and administration. There were a consortium, outsourcing and ultimately the services have been carried out by city employees. At the first place of study, it was found that the city government only offered the services of collection and the waste was taken to an area far from the urban center, it was literally a big rubbish dump. The concern was keeping the waste away from the city center. The second place showed an evolution in the management of services, it had changed from a rubbish dump to a recycling plant with a controlled landfill and at the third place they started with a recycling plant and sorting with a controlled landfill and after they invested in the construction of a sanitary landfill. Panambi has excelled in the region of AMUPLAM, which is part of the way to perform the management of solid waste, although much progress is needed for it to be considered a model.